Atividade antifungica de compostos de cobre, zinco e potássio no crescimento micelial e germinação de conidios de Fusarium solani f. sp. piperis - Santos, Renata Aparecida Ahnert dos (2019)
The search for alternative methods and products of disease management has been increasing in recent years due to the harmful effects that pesticides cause to the environment and to human health. The studies to control fusariosis using alternative methods are related to the strategies of modern agriculture and go towards the economic and ecological interests, being the stimulus to the defense of the plants by the induction of resistance an important alternative. The natural protection of plants against pathogens is given by several mechanisms. It is partly based on a variety of constitutional barriers already present in plant tissues prior to any attack or infection. Micronutrients have been identified as one of the major mineral elements associated with the induction of resistance to plant diseases. Thus, the objective of this study was to test the antifungal activity in vitro using CuSO4, ZnSO4 and KCl against Fusarium solani f. sp. piperis.